2007
DOI: 10.1007/s00018-007-7310-9
|View full text |Cite
|
Sign up to set email alerts
|

Type-2 copper-containing enzymes

Abstract: Type-2 Cu sites are found in all the major branches of life and are often involved in the catalysis of oxygen species. Four type-2 Cu protein families are selected as model systems for review: amine oxidases, Cu monooxygenases, nitrite reductase/multicopper oxidase, and CuZn superoxide dismutase. For each model protein, the availability of multiple crystal structures and detailed enzymological studies provides a detailed molecular view of the type-2 Cu site and delineation of the mechanistic role of the Cu in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 93 publications
1
88
0
2
Order By: Relevance
“…Both marine nirK clades were represented by the sequences retrieved exclusively from epi and bathypelagic seawater, and exhibited high divergence with 'soil' and 'thermophilic' crenarchaeal and bacterial nirK clades (Figure 3). According to the predictions of MacPherson and Murphy (2007), the absence of four histidine residues at positions His 43 , His 87 , His 270 and His 321 (Achromobacter cycloclastes NirK numbering), required for trinuclear copper coordination, strongly suggests that NirK-like proteins of 'marine' lineages are NirKs and not multicopper oxidases. Such His-containing multicopper oxidase (CENSYa_1582) was initially annotated as NirK in the genome of C. symbiosum (Hallam et al, 2006a, b), the marine sponge symbiont, which is actually lacking NirK (Bartossek et al, 2010).…”
Section: Deep-sea Crenarchaeota-specific Genes Encoding Nirkmentioning
confidence: 99%
“…Both marine nirK clades were represented by the sequences retrieved exclusively from epi and bathypelagic seawater, and exhibited high divergence with 'soil' and 'thermophilic' crenarchaeal and bacterial nirK clades (Figure 3). According to the predictions of MacPherson and Murphy (2007), the absence of four histidine residues at positions His 43 , His 87 , His 270 and His 321 (Achromobacter cycloclastes NirK numbering), required for trinuclear copper coordination, strongly suggests that NirK-like proteins of 'marine' lineages are NirKs and not multicopper oxidases. Such His-containing multicopper oxidase (CENSYa_1582) was initially annotated as NirK in the genome of C. symbiosum (Hallam et al, 2006a, b), the marine sponge symbiont, which is actually lacking NirK (Bartossek et al, 2010).…”
Section: Deep-sea Crenarchaeota-specific Genes Encoding Nirkmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] It was suggested that Cu 2+ and several other dications could act as catalysts for the formation of peptide bonds in aqueous solution. 8,9 Cu 2+ can readily move across cell membranes and through ion channels and become toxic at elevated cellular concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing this ET to Cu II M -OOH is functionally required because it would generate Cu I -O(H)OH, which would lead to deleterious Fenton chemistry. The requirement for large λ i offers an explanation for why Nature chose the counterintuitive Cu H site for electron transfer, especially because type 2 His 3 Cu sites are generally used directly for substrate binding and oxidation/reduction in other enzymes (for example, in copper amine oxidase, nitrite reductase, and superoxide dismutase) (33). In particular, if Cu H were replaced by a type 1, blue, copper ET site (with λ i ∼0.35), premature ET leading to Fenton chemistry would be accessible with a rate approaching 0.1 s -1 (SI Appendix, Fig.…”
mentioning
confidence: 99%